Evaluation of smear layer and Ca/P ratio in intra-radicular dentine irrigated with different irrigants adjunct with diode laser - Tarek Abdallah Abdel Salam; Doaa M. Sadony; El-sayed El-tayeb Abdallah; Haidy N. Salem (Bulletin of the National Research Centre)
Abstract Background This study aims to determine the smear layer removal from the root canals using different irrigant solutions with diode laser. Methods A set of sixty human upper incisor teeth were chosen. Access cavity preparation was done followed by canal instrumentation. Samples were divided into six groups (Group A: sodium hypochlorite NaOCl, Group B: NaOCl + diode laser, group C: NaOCl + EDTA ethylene diamine tetra-acetic acid solution, Group D: NaOCl + EDTA + diode laser, Group E: NaOCl + garlic extract, Group F: NaOCl + garlic extract + diode laser. Examining the smear layer removal at the coronal, middle and apical thirds of the root canals was done by using electron microscope analysis. Using an energy-dispersive X-ray, the calcium/phosphorus Ca/P ratio was measured. Results Among the examined groups, there were not any significant differences regarding the smear layer removal. The elimination of smear layers at the middle and coronal thirds was greater in all examined groups than in the apical third. EDX analysis revealed no statistically significant variation between the tested groups. Conclusions Using diode laser with sodium hypochlorite and ethylene diamine tetra-acetic acid irrigant solution was more effective for the elimination of smear layers. Garlic extract could be used as an alternative irrigant solution in debris removal.